Assessment of Patients and Surgeons Satisfaction from Nasal Function and Appearance Following Closed Reduction - Milad Etemadi; Shadi Mohammadi; Mohammad Hossein Nikbakht; Olia Ghazavi (Isfahan University of Medical Sciences, 2022)
Nasal fracture is the most common fracture of the maxillofacial region, so surgeons' and patients' satisfaction after closed reduction from aesthetic and functional (including the effects of respiration and olfaction) perspective is important. The aim of this study was to evaluate the satisfaction of surgeons and patients with the appearance and function of the nose after closed reduction surgery during 6-12 months after surgery to improve the outcomes of this procedure.Materials & Methods:This descriptive-analytical and cross-sectional study was performed on 90 patients in Alzahra and Kashani hospitals of Isfahan during the years 1397-1398 who underwent a closed reduction of nasal fracture within 6-12 months after surgery. All patients and surgeons answered questions about aesthetic and functional outcomes and the need for septorhinoplasty after closed reduction. Pearson correlation coefficient, t-test and paired-sample t-test were used to analyze the data. P value less than 0.05 was considered as a significant level.Results:About 55% of patients were satisfied with the aesthetic outcome and 38.8% expressed they would consider further surgery to correct the residual nasal deformity. The mean score of surgeons' satisfaction for nasal aesthetics and function was 3.74 and 3.50. Surgeons expressed that the patients' requirement for septorhinoplasty is low to moderate.Conclusion:Satisfaction of the patient and the surgeon with the nasal closed reduction was in high-medium range. Also, according to both patients' and surgeons' opinions, requirement for septorhinoplasty surgery has a significant and direct relationship with aesthetic issues and also obstruction of the airway following a nasal bone fracture